Arab Countries in Transition : Economic Outlook and Key Challenges. (Policy Papers; Policy Paper ;, 2013)
Arab Countries in Transition (ACTs) continue to face high political uncertainty and social pressures. The uprisings and protests have generated the promise of a better life for 300 million people, but forthcoming elections and constitutional reform, as well as populations anxious for jobs and higher incomes, complicate policymaking for many governments. At the same time, fiscal and reserves buffers have diminished sharply, underscoring the urgent need to maintain macroeconomic stability in an environment of sluggish global growth, high commodity prices, and still impaired domestic confidence. Resolute policy action and support from the international community are required; particularly as last year's subdued growth in the ACTs (except Libya) is expected to improve only slightly in 2013 and is overshadowed by persistent external and regional risks. It will be equally important for policymakers to move quickly on designing and implementing effective structural reforms to build dynamic and inclusive economies that generate (many) more jobs than are available today. Promoting private-sector growth and international trade, as well as attracting foreign direct investment inflows, will be key components of success. Financial assistance and technical expertise from external partners, including Transition Fund projects, can make a big difference in this endeavor.